Impedance Model of Immune Reaction Leading to NETosis. (2015) - Schröter, Anna; Rösen-Wolff, Angela; Gerlach, Gerald
Abstract: The so-called NETs (neutrophil extracellular traps) are found in vast amounts in inflamed wounds and are therefore a good marker for wound infections. They are a product of an immune reaction. Their integrant DNA has a certain dielectric behavior due to its charge. This allows a direct electric determination without the need of a transducer. Human neutrophils were used to measure the release of NETs in vitro . However, the structural changes of the cells during this process have to be taken into account. In this work a model was developed which reflects these changes. This model was compared with impedance measurements. We found that changes in the medium composition strongly modify the dielectric behavior of the system. The most obvious change here is caused by the appearance of the NETs. These changes remain also stable after the cells died and did not undergo more structural changes. The measurement of NETs is a very promising approach to support the diagnosis of inflammation processes especially in wounds.